La gamificación como estrategia para potenciar habilidades cognitivas y motivación intrínseca en estudiantes de quinto año de educación básica en la escuela de educación básica Luis Aurelio González de la cuidad de Guaranda, provincia Bolívar, durante los meses octubre 2023 a febrero 2024 - Bazantes Guillen, Lourdes Fernanda (2024)
Gamification emerges as an innovative strategy in the educational context to enhance cognitive skills and intrinsic motivation in fifth-grade elementary students. However, it is evident that some students face obstacles in adapting to this methodology, which can affect their participation and academic performance. It is crucial for educators to recognize these barriers and develop pedagogical strategies to effectively integrate gamification into the educational process. Gamification leverages game dynamics, such as challenges and rewards, to stimulate cognitive skills such as critical thinking and problem-solving. However, many teachers have limited information about this strategy, which affects their ability to support students. It is necessary to address this lack of knowledge through educational initiatives that raise awareness and train educators. Gamification, cognitive skills, and intrinsic motivation must be supported by ICT to provide teachers with dynamic tools that enhance learning. The use of online games can be beneficial for learning, as it promotes the development of cognitive skills and intrinsic motivation. The findings from interviews and surveys highlight the importance of gamification training in educational institutions, as well as the need for adequate resources for effective implementation